2012
DOI: 10.1039/c2cc31340e
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a flexible tethered porphyrin dimer that preferentially complexes fullerene C70

Abstract: A simple, high yield, two-step synthesis yields a porphyrin dimer linked by a flexible dithiol tether that preferentially binds fullerene C70 over C60 in toluene solution. The complex forms stable aggregates when cast on glass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…The significantly larger association constant of 1 for C 70 versus C 60 ( K C60 / K C70 =678) further revealed that cyclic bisporphyrin 1 is effective for selective C 70 inclusion. The value is also significantly higher than those of previously reported,, fullerene receptors (Table S2). Fascinated by this excellent ability of 1 to bind C 70 , we investigated the selective extraction of C 70 from C 60 /C 70 fullerene mixtures.…”
Section: Resultscontrasting
confidence: 65%
“…The significantly larger association constant of 1 for C 70 versus C 60 ( K C60 / K C70 =678) further revealed that cyclic bisporphyrin 1 is effective for selective C 70 inclusion. The value is also significantly higher than those of previously reported,, fullerene receptors (Table S2). Fascinated by this excellent ability of 1 to bind C 70 , we investigated the selective extraction of C 70 from C 60 /C 70 fullerene mixtures.…”
Section: Resultscontrasting
confidence: 65%
“…26). 51 Upon mixing the dimer with C 60 and C 70 we discovered that it preferentially binds with fullerene C 70 over C 60 in toluene solution. The dimer–fullerene complex also forms stable aggregates when casted on glass.…”
Section: Substituted Fluorinated Porphyrinoids For Application In Matmentioning
confidence: 99%
“…For example, disrupting the uniformity of the system or over-modifying a fullerene derivative may undermine its electric and biomedical properties. 6 It is particularly noted that the optimization of one organic device is relatively complex. Herein, we have developed a facile approach to optimize a photodetector device simply by substituting the traditional substrate with wavelength matched photonic crystals (PCs).…”
Section: Introductionmentioning
confidence: 99%